2022
DOI: 10.1002/cmdc.202100603
|View full text |Cite
|
Sign up to set email alerts
|

5’‐Phosphorylation Increases the Efficacy of Nucleoside Inhibitors of the DNA Repair Enzyme SNM1A

Abstract: Certain cancers exhibit upregulation of DNA interstrand crosslink repair pathways, which contributes to resistance to crosslinking chemotherapy drugs and poor prognoses. Inhibition of enzymes implicated in interstrand crosslink repair is therefore a promising strategy for improving the efficacy of cancer treatment. One such target enzyme is SNM1A, a zinc co-ordinating 5'-3' exonuclease. Previous studies have demonstrated the feasibility of inhibiting SNM1A using modified nucleosides appended with zinc-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 35 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…We demonstrate unambiguously that MGME1 prefers to interact with the 5′-end of an ssDNA substrate and that a 5′-phosphate contributes to the optimal DNA binding and catalysis of MGME1. A close examination of the X-ray crystal structures of MGME1 did not show any apparent phosphate-binding pocket, unlike other 5′-exonucleases, such as human SNM1B ( 29 ). Rather, we found that several motifs could potentially mediate the interactions with phosphates on the basis of the electrostatic potential analysis ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…We demonstrate unambiguously that MGME1 prefers to interact with the 5′-end of an ssDNA substrate and that a 5′-phosphate contributes to the optimal DNA binding and catalysis of MGME1. A close examination of the X-ray crystal structures of MGME1 did not show any apparent phosphate-binding pocket, unlike other 5′-exonucleases, such as human SNM1B ( 29 ). Rather, we found that several motifs could potentially mediate the interactions with phosphates on the basis of the electrostatic potential analysis ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…[11c] Fragments identified during this proof-of-concept assay correspond to metal-binding groups that have previously been recognised by SNM1A. [7][8]11] This demonstrates that fragment-based screening is a suitable approach for the identification of metal-binding groups suitable for targeting this enzyme.…”
Section: Chembiochemmentioning
confidence: 90%
“…Although screens of bioactive molecules have previously succeeded in identifying several inhibitors of SNM1A, [6,10] there is currently no screening method focused solely on the identification of metalbinding groups, which have been demonstrated as being key for targeting SNM1A. [7][8]11] Fragment-based screening approaches evaluate the ability of low-molecular-weight molecules to exert a desired biological action. [12] Although the fragments themselves may only have low binding affinity for the desired target, they can be combined with other scaffolds or functional groups to create a final drug molecule or tool compound with high binding affinity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations